2018
DOI: 10.1139/cjpp-2016-0445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovariectomy on antioxidant defence systems in the right ventricle of female rats with pulmonary arterial hypertension induced by monocrotaline

Abstract: The aim of this study was to evaluate the impact of ovariectomy on oxidative stress in the right ventricle (RV) of female rats with pulmonary arterial hypertension (PAH) induced by monocrotaline (MCT). Rats were divided into four groups (n=6/group):sham (S), sham + MCT (SM), ovariectomized (O), and ovariectomized + MCT (OM).MCT (60 mg/kg i.p) was injected 1 week after ovariectomy or sham surgery. Three weeks after,, echocardiographic analysis and RV catheterisation were performed. RV morphometric, biochemical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Taguchi et al found that serum GGT could reflect the antioxidant properties in healthy Japanese men (29). Interestingly, a research from Siqueira et al showed that in female rats with PAH by ovariectomy, GGT could affect the oxidative stress and antioxidant system via estrogen (30). So, one of possible reasons was "estrogen withdrawal, " alleviating protective role of estrogen (E2) against oxidative damage (31).…”
Section: Discussionmentioning
confidence: 99%
“…Taguchi et al found that serum GGT could reflect the antioxidant properties in healthy Japanese men (29). Interestingly, a research from Siqueira et al showed that in female rats with PAH by ovariectomy, GGT could affect the oxidative stress and antioxidant system via estrogen (30). So, one of possible reasons was "estrogen withdrawal, " alleviating protective role of estrogen (E2) against oxidative damage (31).…”
Section: Discussionmentioning
confidence: 99%
“…In rats treated with monocrotaline to increase pulmonary artery pressure without inducing RV hypertrophy, RV hydrogen peroxide increases but SOD, catalase, and glutathione peroxidase activities are also enhanced (Siqueira et al, 2018).…”
Section: Ros Defense Systems In Rvmentioning
confidence: 99%